Inhibition of CREB-CBP Signaling Improves Fibroblast Plasticity for Direct Cardiac Reprogramming - Bektik, Emre (Cells, 2021)
Direct cardiac reprogramming of fibroblasts into induced cardiomyocytes (iCMs) is a promising approach but remains a challenge in heart regeneration. Efforts have focused on improving the efficiency by understanding fundamental mechanisms. One major challenge is that the plasticity of cultured fibroblast varies batch to batch with unknown mechanisms. Here, we noticed a portion of in vitro cultured fibroblasts have been activated to differentiate into myofibroblasts, marked by the expression of αSMA, even in primary cell cultures. Both forskolin, which increases cAMP levels, and TGFβ inhibitor SB431542 can efficiently suppress myofibroblast differentiation of cultured fibroblasts. However, SB431542 improved but forskolin blocked iCM reprogramming of fibroblasts that were infected with retroviruses of Gata4, Mef2c, and Tbx5 (GMT). Moreover, inhibitors of cAMP downstream signaling pathways, PKA or CREB-CBP, significantly improved the efficiency of reprogramming. Consistently, inhibition of p38/MAPK, another upstream regulator of CREB-CBP, also improved reprogramming efficiency. We then investigated if inhibition of these signaling pathways in primary cultured fibroblasts could improve their plasticity for reprogramming and found that preconditioning of cultured fibroblasts with CREB-CBP inhibitor significantly improved the cellular plasticity of fibroblasts to be reprogrammed, yielding ~2-fold more iCMs than untreated control cells. In conclusion, suppression of CREB-CBP signaling improves fibroblast plasticity for direct cardiac reprogramming.